Leptospira spp. antibodies in captive coatis (Nasua nasua Storr, 1780) (Carnivora: Procyonidae) - Langoni, Helio [UNESP]; Kawaguchi, M. F. [UNESP]; Oshika, J. C. [UNESP]; Da Silva, R. C. [UNESP]; Teixeira, C. R. [UNESP] (FapUNIFESP (SciELO), 2009)
Leptospirosis is a worldwide infection that affects many species, including wild animals. The present study aimed to detect Leptospira spp. antibodies in 17 captive coatis (Nasua nasua) by the microscopic agglutination test (MAT). Nine (52.94%) animals tested positive and the following serovars were identified: Copenhageni (22.22%), Shermani (22.22%), Andamana (11.11%), Wolfii (11.11%) and Pyrogenes (11.11%). Two samples presented coagglutination, one (11.11%) for Hebdomadis and Wolfii, and another (11.11%) for Hebdomadis, Hardjo and Wolfii. The current study revealed the presence of the infection even in animals without any clinical signs, reinforcing the possibility that wild animals in captivity may be infected by leptospire serovars, thus enabling reservoirs.
Keywords: Antibodies; Captive coatis; Leptospira spp.; Microscopic agglutination test; Nasua nasua